THE LAW APPROVING TREATIES (“UU PENGESAHAN”): WHAT DOES IT SIGNIFY? - Agusman, Damos Dumoli (Jurnal Bina Mulia Hukum, 2016)
ABSTRACTThe provisions in Article 11 of the Constitution of 1945 and Laws of the International Treaties generally requires the "consent" of the House of Representatives (DPR) in the making and ratification of the treaty. The difference between the two is that the rules referred to in Article 11 of Constitution of 1945 does not specifically mention the form of approval, while the Laws of the International Treaties requires that the ratification of a treaty is done by Act or by Presidential Decree. The big difference in the process of ratification of the treaty to be applied in the national legal system of Indonesia, has been controversial, both among academics and practitioners, such as the theory of monism-dualism on International Law and National Law, the status of an international treaty into national laws of Indonesia, and the implementation of international agreements in Indonesia. This article is intended to explain the process of ratification of an international agreement, differences that occur, as well as the ratification of the treaty practice lasted this long.Keywords: international law, legislation, monism-dualism, treaties, ratificationABSTRAKKetentuan dalam Pasal 11 Undang-Undang Dasar 1945 dan Undang-Undang Perjanjian Internasional secara umum mensyaratkan adanya “persetujuan” dari Dewan Perwakilan Rakyat (DPR) dalam pembuatan maupun pengesahan perjanjian internasional. Perbedaan antara kedua aturan dimaksud adalah bahwa dalam Pasal 11 Undang-Undang Dasar 1945 tidak secara khusus mensyaratkan bentuk dari persetujuan dimaksud, sementara Undang-Undang Perjanjian Internasional mensyaratkan bahwa pengesahan perjanjian internasional dilakukan dengan Undang-Undang atau Keputusan Presiden. Adanya perbedaan tentang proses pengesahan perjanjian internasional untuk dapat diberlakukan dalam sistem hukum nasional Indonesia, akhirnya telah menimbulkan perdebatan, baik di kalangan akademisi maupun praktisi, antara lain teori monisme-dualisme tentang Hukum Internasional dan Hukum Nasional, status suatu perjanjian internasional dalam hukum nasional Indonesia, maupun implementasi dari perjanjian internasional di Indonesia. Artikel ini dimaksudkan untuk menjelaskan proses pengesahan suatu perjanjian internasional, perbedaan pandangan yang terjadi, serta praktik pengesahan perjanjian internasional yang berlangsung selama ini.Kata Kunci: hukum internasional, legislasi, monisme-dualisme, perjanjian internasional, ratifikasiDOI :  https://doi.org/10.23920/jbmh.v1n1.8